(untitled) (Revisão de Sociologia Clínica, 2025)
Reflecting on the experience of a sociological evaluation about a community Carer Café project by Hong Kong Federation of Women’s Centre between 2022 and 2023, this paper illustrates why and how developing a deliberative researcher-practitioner relationship in the evaluation research is of importance to making a more profound impact on service development and knowledge transfer. The collaboration includes engagement, mutual learning, dialogue in the evaluation, and the deliberation of knowledge for service development, and re-positioning the roles between researchers and practitioners in further collaboration. The reflection provides a practical account of how to address the power imbalance in the evaluation process and facilitates the deliberation in the sociological evaluation research. From the reflection, this article also highlights recommendations on how to work out deliberative clinical sociological evaluation research.